Multidimensional Leadership Moderates The Influence Of Motivational Agility And Self-confidence in Abilities On Civil Servant Performance In West Kotawaringin, Central Kalimantan, Indonesia - Juni Gultom, Juni Gultom; Budiyanto, Budiyanto; Suhermin, Suhermin (Al-Makki Publisher, 2023)
This study used the goal-setting theory as a theoretical perspective to empirically investigate the role of multidimensional leadership as a moderator in influencing motivational agility and self-confidence in abilities on civil servant performance. The respondents were 308 civil servants in West Kotawaringin, Central Kalimantan. The data were processed using PLS Structural Equation Modeling (SEM). This study proposes multidimensional leadership as a strategy to improve civil servant performance. The results show that motivational agility and self-confidence in abilities influence civil servant performance, and multidimensional leadership plays a role in strengthening civil servant performance. These results strengthen the goal-setting theory which states that employees who have a high commitment to goals will be encouraged to increase their efforts to achieve those goals.